CRY1‐CBS binding regulates circadian clock function and metabolism. (9th June 2020) - Cal‐Kayitmazbatir, Sibel; Kulkoyluoglu‐Cotul, Eylem; Growe, Jacqueline; Selby, Christopher P.; Rhoades, Seth D.; Malik, Dania; Oner, Hasimcan; Asimgil, Hande; Francey, Lauren J.; Sancar, Aziz; Kruger, Warren D.; Hogenesch, John B.; et al.
Abstract : Circadian disruption influences metabolic health. Metabolism modulates circadian function. However, the mechanisms coupling circadian rhythms and metabolism remain poorly understood. Here, we report that cystathionine β‐synthase (CBS), a central enzyme in one‐carbon metabolism, functionally interacts with the core circadian protein cryptochrome 1 (CRY1). In cells, CBS augments CRY1‐mediated repression of the CLOCK/BMAL1 complex and shortens circadian period. Notably, we find that mutant CBS‐I278T protein, the most common cause of homocystinuria, does not bind CRY1 or regulate its repressor activity. Transgenic Cbs Zn/Zn  mice, while maintaining circadian locomotor activity period, exhibit reduced circadian power and increased expression of E‐BOX outputs. CBS function is reciprocally influenced by CRY1 binding. CRY1 modulates enzymatic activity of the CBS. Liver extracts from Cry1 −/− mice show reduced CBS activity that normalizes after the addition of exogenous wild‐type (WT) CRY1. Metabolomic analysis of WT, Cbs Zn/Zn, Cry 1 −/−, and Cry2 −/− samples highlights the metabolic importance of endogenous CRY1. We observed temporal variation in one‐carbon and transsulfuration pathways attributable to CRY1‐induced CBS activation. CBS‐CRY1 binding provides a post‐translational switch to modulate cellular circadian physiology and metabolic control. Abstract : The mechanisms coupling circadian rhythms and metabolism remain poorly understood. We find that the core circadian protein cryptochrome 1 (CRY1) binds cystathionine β‐synthase (CBS), a central enzyme in one‐carbon metabolism. This binding modulates the activity of both proteins. During the active phase, CBS augments CRY1‐mediated repression of BMAL1/CLOCK‐driven transcription. During the rest phase, CRY1 increases CBS enzymatic activity.